The Zune pocket guide - Farkas, Bart (Peachpit Press, 2006)
Microsoft, with its Zune music player and software, will seek to break Apple's hold on the portable-player market. Through distinctive community-building features along with wireless connectivity, Microsoft is creating with Zune the same level of excitement as it has with Xbox. Zune users will want to start using their player and music store as soon as they are available, and this guide will show them how. In these pages, trusted gadget teacher and best-selling Podcasting author Bart Farkas reveals the secrets to using the new Zune portable player and music software. Farkas offers the quickest way to learn the main features, such as finding music in the Zune music store, seeing and making recommendations, viewing other Zune users' playlists, using the player, shopping for music and videos, troubleshooting advice, and more. The low-priced Zune Pocket Guide will an essential companion for all Zune users.